2003
DOI: 10.1086/367639
|View full text |Cite
|
Sign up to set email alerts
|

On the Rotational Evolution of Solar‐ and Late‐Type Stars, Its Magnetic Origins, and the Possibility of Stellar Gyrochronology

Abstract: We propose a simple interpretation of the rotation period data for solar-and late-type stars. The open cluster and Mt. Wilson star observations suggest that rotating stars lie primarily on two sequences, initially called I and C. Some stars lie in the intervening gap. These sequences, and the fractional numbers of stars on each sequence evolve systematically with cluster age, enabling us to construct crude rotational isochrones allowing 'stellar gyrochronology', a procedure, upon improvement, likely to yield a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
797
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 635 publications
(844 citation statements)
references
References 65 publications
38
797
3
Order By: Relevance
“…In agreement with the paradigm advanced by Barnes (2003a), M09 found that M 35 stars group into two main subpopulations that lie on narrow sequences in a colour-period diagram (see Fig. 6).…”
Section: Rossby Numbers and Rotation Sequences In M 35supporting
confidence: 79%
See 3 more Smart Citations
“…In agreement with the paradigm advanced by Barnes (2003a), M09 found that M 35 stars group into two main subpopulations that lie on narrow sequences in a colour-period diagram (see Fig. 6).…”
Section: Rossby Numbers and Rotation Sequences In M 35supporting
confidence: 79%
“…A strong gradient in angular velocity between the radiative core and the convective envelope is an essential ingredient for the generation of magnetic field at the base of the convection zone and magnetic fields are quite effective at transporting angular momentum (Spruit 2002). In line with the above discussion, Barnes (2003a) proposed that the C sequence is due to the coupling of the stellar wind to just the convective zone that is decoupled from the radiative zone, while the I sequence is due to the coupling of the wind with the entire star. The transition across the gap between these two rotation sequences would therefore be associated with a coupling between the radiative and the convective zone.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The M48 cluster is much older and predominantly consists of stars that have converged onto the main rotation sequence. These same features are seen in other clusters of various ages (Barnes 2003). The cluster members move toward a single well-defined main rotation sequence as the cluster ages.…”
Section: Main-sequence Rotationsupporting
confidence: 72%